Altered serum antibody levels in children with periodic fever, aphthous stomatitis, pharyngitis, and cervical adenitis - Umut Gazi; Ceyhun Dalkan; Burcin Sanlidag; Zeynep Cerit; Ilke Beyitler; Nerin Narin Bahceciler (Archives of Rheumatology, 2024)
Objectives: This study aimed to extend the literature by analyzing immunoglobulin (Ig) A, IgE, IgG, IgG2, IgG3, and IgM antibody levels in periodic fever, aphthous stomatitis, pharyngitis, and cervical adenitis (PFAPA) patients. Patients and methods: This study retrospectively analyzed the antibody test results of 20 pediatric patients (10 males, 10 females; mean age: 2.5±1.5 years; range, 0.5 to 5.4 years) with and without flare who were initially evaluated for a number of underlying diseases due to periodic fever/infectious symptoms but then diagnosed with PFAPA between January 2015 and December 2020. Antibody levels were determined by chemiluminescence microparticle immunoassay. The results were retrospectively compared with a group of healthy children after the PFAPA diagnosis was confirmed. Results: The chemiluminescence microparticle immunoassay revealed 35%, 65%, 20%, 86.6%, and 55% of PFAPA cases with low serum levels of IgA, IgG, IgG2, IgG3, and IgM respectively, while 56.2% had high IgE levels. Moreover, low serum levels of at least two antibody classes or subclasses were reported in 80% of the PFAPA children. While cases with low IgG serum levels were with the highest incidence rates among the low IgG3 PFAPA patient population, both high IgE and low IgM cases were common in the rest of the patients. Conclusion: Our results suggest an association between PFAPA and low serum antibody levels, particularly of IgG3. Future studies are needed to confirm our conclusion.